Genetic Analysis of Different Amylose Levels in Rice - Kumar, Ish; Khush, G.S. (Wiley, 1987)
Amylose content has a pronounced effect on the cooking and eating quality of rice (Oryza sativa L.). Inheritance of amylose content in five crosses of rice and their reciprocals involving low, intermediate, and high amylose parents was studied. The analysis was based on single grains in the parent, F1, F2, B1F1 and B2F1 generations. The genes for high amylose content were found to be completely dominant over those for low or intermediate amylose content. Low or intermediate amylose content in the crosses tested was found to be governed by a single gene having a major effect. Evidence that amylose content was also influenced by genes of minor effects, or modifiers, was also noted. The role of dosage effects in influencing segregation was stated and breeding strategies are discussed.